A NEW DEFORMATION OF W-INFINITY AND APPLICATIONS TO THE 2-LOOP WZNW AND CONFORMAL AFFINE TODA MODELS - Aratyn, H.; Ferreira, L. A.; Gomes, J. F.; Zimerman, A. H. (Elsevier B.V., 1992)
We construct a centerless W-infinity type of algebra in terms of a generator of a centerless Virasoro algebra and an abelian spin 1 current. This algebra conventionally emerges in the study of pseudo-differential operators on a circle or alternatively within KP hierarchy with Watanabe's bracket. Construction used here is based on a spherical deformation of the algebra w(infinity) of area preserving diffeomorphisms of a 2-manifold. We show that this deformation technique applies to the two-loop WZNW and conformal affine Toda models, establishing henceforth W(infinity) invariance of these models.